Ophthalmology Residents' Internship Selection and Initial Trainee Confidence: An Observational Study - Logothetis, Hercules D.; Pyatetsky, Dmitry; Baqai, Jeanine A.; Volpe, Nicholas J. (Journal of Academic Ophthalmology, 2018)
Purpose In this study, we set out to better understand the factors that influenced current ophthalmology residents' internship selection. We then tested the hypothesis that certain clinical or research experiences in medical school and internship may influence residents' confidence upon entering ophthalmology residency. Furthermore, we investigated whether completing internship at the same program as one's residency is correlated with confidence at the start of residency.Design Observational, cross-sectional, multicenter survey.Participants U.S. ophthalmology residents (Post Graduate Year 2/3) belonging to the class of 2018. Eighty surveys were submitted of which 63 were analyzed based on established inclusion criteria.Methods Residents responded to a 22-question online survey addressing how residents chose their internship, internship curriculum, exposure to ophthalmology in medical school and during internship, confidence level entering ophthalmology residency, confidence in managing various ocular pathologies, and factors that built confidence prior to ophthalmology residency. A Likert scale format was used for the majority of survey questions. Kruskal–Wallis testing and Fisher's exact testing were used to compare outcome variables among three groups defined by sense of confidence entering ophthalmology training.Main Outcome Measures Level of confidence at the start of ophthalmology residency.Results Quality of life and geographic location were found to be the most important factors in choosing internship programs, while obtaining ophthalmology skills was least. Although 32.3% of residents either agreed or strongly agreed that they felt confident at the start of ophthalmology residency, 42.9% disagreed or strongly disagreed. Residents who felt most confident for ophthalmology training spent more time on ophthalmology rotations in medical school (p = 0.05) or internship (p = 0.02) and worked up patients independently during their internship ophthalmology rotation (s) (0.01). Completing one's internship at the same institution as one's ophthalmology residency did not correlate with confidence entering residency.Conclusions Residents chose internships based on quality-of-life factors rather than enhancing ophthalmology training. Residents who felt confident at the start of ophthalmology residency had more hands on clinical ophthalmology experience than residents who did not feel confident. No statistically significant correlation was found between completion of internship at the same institution as one's ophthalmology residency and confidence entering residency.
Keywords: internship; ophthalmology residency; confidence level